Sustainability outcomes of the United States food system - C. B. Knox; Shelie Miller (Journal of Agriculture, Food Systems, and Community Development, 2022)
Food systems literature has shifted towards interdisciplinarity and the use of systems lenses but can still be disjointed and unconnected. To bring together disciplinary knowledge and establish a common understanding of food systems, we conducted a systematic review to inventory sustainability outcomes of the U.S. food system. The literature search returned 2,866 articles, which was reduced to 49, reviewed here. A qualitative content analysis process identified 93 outcomes. These were split across three main themes of environmental, socio-economic, and health outcomes. This review also identified several trends in food systems literature, such as an underrepresentation of socio-economic outcomes and a lack of inclusion of social outcomes in natural science journals. The sustainability outcomes inventoried here may help to facilitate greater communication and collaboration in food systems research and situate current and future food systems studies within this inventory.